Optimasi Kapasitasi Produksi Untuk Memperoleh Keuntungan Maksimum dengan Linear Programming Metode Simpleks : (Studi Pada UMKM Minuman Alltho) - Dinda Fatimah Sarah; Yosika Dian Saputri; Putri Hazmawati; Pradita Eko Prasetyo Utomo; Ulfa Khaira (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2024)
This research is a progress report of the project entitled "Optimization of Production Capacitation to Obtain Maximum Profit with Linear Programming Simplex Method (Study on Alltho Beverage UMKM)". This project aims to help the owner of Alltho Micro, Small, and Medium Enterprises (MSMEs) in optimizing the production and profit of their products. In this study, the linear programming method with the simplex method technique was used to find the optimal solution that maximizes the profits of Alltho UMKM. Data on the maximum capacity of raw materials and product selling prices are determining factors in the calculation. The three main products analyzed were Red Velvet Choco Royal, Choco Royal Oreo, and Greentea Choco Royal. The results showed that using the linear programming simplex method, the optimal production quantities of each product were 10.29 Red Velvet Choco Royal drinks and 11.76 Greentea Choco Royal drinks, while the production of Choco Royal Oreo should be temporarily stopped. These results indicate that Alltho MSMEs can achieve maximum profits of around IDR 227,942 by producing these products according to the recommended quantities. This research provides an important contribution to decision-making in MSME production management, helps improve efficiency in resource utilization, and provides an overview of the importance of applying mathematical techniques in optimizing MSME businesses in a competitive era.